Gender Ambivalence in Hamka’s Tafsir al-Azhar: Between Islamic ‎Modernism and Patriarchal Tradition in Gender Relations - Muhammad Naufal Hakim; Mas Tajuddin Ahmad; Devi Eka Diantika; Nilna Indriana; Nurul Musyafaah; Murdiono Murdiono (Jurnal Ulunnuha, 2026)
This study examines gender ambivalence in Hamka’s interpretation of gender-related Qur’anic verses in Tafsir al-Azhar. While previous studies have generally portrayed Hamka either as a modernist reformer or as an exegete who reproduces patriarchal views, little attention has been paid to the ambivalent character of his interpretations of gender relations and the socio-epistemological factors shaping them. Addressing this gap, the study aims to analyze how Islamic modernist ideals and patriarchal traditions coexist within Hamka’s interpretation of gender-related Qur’anic verses. Employing discourse analysis and Karl Mannheim’s sociology of knowledge, the study investigates Hamka’s interpretations of Q. al-Baqarah [2]: 222–223 and 282, as well as Q. al-Nisā’ [4]: 1 and 34. The findings reveal a pattern of gender ambivalence in which egalitarian and patriarchal tendencies operate simultaneously. In some interpretations, Hamka reinforces male authority and women’s subordinate positions, while in others he emphasizes reciprocity and mutual responsibility, and critiques patriarchal practices. This ambivalence emerges from the interaction of three factors: a predominantly textual-reflective interpretive approach that seeks limited contextualization, a stronger concern with the maqāṣid of the verses than with theorizing gender relations, and the influence of Hamka’s socio-historical background, particularly the encounter between Islamic modernism and Minangkabau cultural traditions. By conceptualizing gender ambivalence as an analytical framework for examining tensions between egalitarian and patriarchal tendencies in Qur’anic interpretation, this study contributes to the field of Qur’anic gender studies. It demonstrates how socio-historical contexts shape the production of exegetical discourse.